Sistema de Administración de Propiedad Horizontal (Appartment) (2023)
In places like Bogotá, every day it is easier to find a wide variety of complexes and buildings that present problems when keeping track of the people who visit the facilities, given that these processes are recorded manually and are often lost. the records carried out by residents and security guards.